Anthracycline extravasation injuries: management with dexrazoxane - Karin Jordan; Timo Behlendorf; Franziska Mueller; Hans-Joachim Schmoll (Dove Medical Press, 2009)
Karin Jordan, Timo Behlendorf, Franziska Mueller, Hans-Joachim SchmollClinic for Internal Medicine IV, Department for Oncology and Haematology, University Hospital Halle, Halle, GermanyAbstract: The application of anthracyclines in anticancer therapy may result in accidental extravasation injury and can be a serious complication of their use. Tissue necrosis with skin ulceration is a possible outcome in the inadvertent extravasation of anthracyclines during intravenous administration. Until recently, there has been no effective treatment against the devastating effect of extravasated anthracycline. Preclinical and clinical studies are leading to the clinical implementation of dexrazoxane as the first and only proven antidote in anthracycline extravasation. In two multicenter studies dexrazoxane has proven to be highly effective in preventing skin necrosis and ulceration. This review focuses on the development and management of dexrazoxane in anthracycline extravasation injuries. Keywords: dexrazoxane, extravasation, necrosis, anthracyclines